The impact of burnout toward affective commitment and turnover intention - Daffa Rashad Mahmod; Reni Rosari (Jurnal Siasat Bisnis, 2020)
This study aims to examine the influence of burnout components which consist of exhaustion, cynicism and reduced professional efficacy toward affective commitment and turnover intention on the study of supporting division employees in PT. XYZ. This research uses quantitative research design with survey method and use questionnaire as research instrument. Multiple linear regression method is used to test the hypothesis in this research. The results show that although the burnout components of cynicism and reduced professional efficacy have significant and negative effect on affective commitment, the exhaustion component has no effect on affective commitment. The results also proved that exhaustion, cynicism and reduced professional efficacy have significant and positive effect on turnover intention.